(untitled) (Al-Academy, 2022)
The study investigates the possibility of utilizing public interactive sculptures to enhance physical activity in Saudi Arabia. The paper uses a descriptive-analytical methodology to identify the characteristics of interactive sculptures promoting physical activity in public areas as follows: The size and space of the work area are appropriate to the type of physical activity that is achieved, and the importance of the work site in the city and its relation to the surrounding space, identifying participants at the same time and their relationship to ensure safe interaction, as well as the relationship between the esthetic and intellectual concept of working in the community. The study concludes that three technical proposals were presented for interactive sculpture works to be carried out in public places in Riyadh, which allows the public to practice some physical activity when interacting with the work units, thus contributing to enhancing the practice of the community members of physical activity. Within an urban environment, works of Art derive their artistic idea from the Saudi society’s symbolism, values, and culture.